Representasi Kepemimpinan Presiden Joko Widodo Pada Berita Korupsi di Media Indonesia (President Joko Widodo's Leadership Representation on Corruption News in Indonesian Media) - Saiyidinal Firdaus (Jurusan Tadris Bahasa Indonesia, 2022)
Indonesia ranks 89th out of 180 countries and is still a corrupt country. As the leader of the country, the president is expected to make Indonesia no longer a corrupt country. This study seeks to analyze corruption news in the March 31, 2019 edition of Media Indonesia in order to raise views on Joko Widodo as a social actor. This can be known through the analysis of language structure, cognitive processes, and the meaning of discourse based on the context of the